Pengaruh Jumlah Wisatawan, Jumlah Objek Wisata terhadap Pendapatan Asli Daerah Kabupaten Lombok Utara - Fathur Rahman; Suprianto Suprianto; Wahiddin Wahiddin (Jurnal Riset Ekonomi dan Akuntansi, 2024)
This research aims to analyze "The Influence of the Number of Tourists, Number of Tourist Attractions on Original Regional Income of North Lombok Regency". The type of research used in this research is quantitative research with an associative approach. The type of data used in this research is time series data. The data was processed using the Eviews version 10 application using the Multiple Linear Regression analysis method. The results of this research show that partially the independent variable Number of Tourists (X1) has a significant effect on the dependent variable, namely Regional Original Income (Y). Meanwhile, the variable Number of Tourist Attractions (X2) has no significant effect on Original Regional Income (Y). Simultaneous test results Test (F) found that the independent variables (Number of Tourists and Number of Tourist Attractions) did not have a significant effect on the dependent variable, namely Regional Original Income (Y) of North Lombok Regency.